Pengaruh Metode Inkuiri Terhadap Kemampuan Berfikir Kreatif Siswa Pada Mata Pelajaran IPA Kelas V Sekolah Dasar - Risti, Yunita; Ain, Siti Quratul (Jayapangus Press, 2025)
Students' creative thinking abilities are basically still relatively lacking and need to be trained so that they can create a sense of enthusiasm in students, especially in science learning. In this problem, the role of the teacher is very necessary to overcome it by using appropriate learning methods, because teachers play an important role in education and helping students overcome problems in learning. The aim of this research is to determine the effect of the inquiry method on improving students' creative thinking abilities in the fifth grade science subject at UPT SDN 023 Pandau Jaya. The type of research that will be used in this research is Quantitative. This research applies an experimental design using a type of preexperimental design, namely the one group pretest-posttest design method. In this research, the sampling technique used was a purposive sampling technique with a total sample of 22 students from class VA. The data collection technique in this research used a questionnaire. The research instrument in this study was a questionnaire sheet. The data analysis technique used is the paired sample t-test. Research shows that the inquiry method significantly improves students' creative thinking abilities in class V science subjects at UPT SDN 023 Pandau Jaya, as shown by the significance value (Sig. 2-tailed) <0.000 which is smaller than the 0.05 significance level. This approach encourages students to actively explore, ask and analyze, thus supporting the development of creative ideas and innovative problem solving. The inquiry method is proven to be an effective learning strategy for improving the quality of learning and students' higher order thinking skills.